ANALISIS FILM NANTI KITA CERITA TENTANG HARI INI - Asti Haningtyas, S.I.Kom, M.I.Kom, Asti Haningtyas, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2022)
The film industry is booming right now, especially in Indonesia. As a means of entertainment and conveying messages to the public, various cinema themes have been produced. This study aims to qualitatively analyze the content (content analysis) in the exposure of the film